Results of Intravitreal Bevacizumab as an Adjunct to mETDRS Grid Laser in Diabetic Macular Edema: Doi: 10.36351/pjo.v37i1.1135 - Khanzada, Mahtab Alam; Ahmed, Munawar; Mirza, Azfar Ahmed; Mari, Ghazi Khan; Mahmood, Muhammad Arshad (Pakistan Journal of Ophthalmology, 2020)
Purpose: To assess the efficacy of Intravitreal Bevacizumab as an adjuvant to grid laser photocoagulation in patients with diffuse macular edema (DME) in type II diabetes. Study Design: Quasi experimental study. Place and Duration of Study: Institute of ophthalmology, Liaquat University of Medical and Health Sciences, Jamshoro, from September 2016 to November 2018 Methods: Ninety five patients with diffuse macular edema in type II diabetes were selected by convenient sampling. Group I patients were treated with ETDRS grid laser photocoagulation. Group II patients were treated with ETDRS grid laser photocoagulation followed by intravitreal bevacizumab after one week monthly for 2 months and then as per need. All patients were examined after 1st, 2nd and 3rd month and mean change in best corrected visual acuity (BCVA) and central macular thickness (CMT).Statistical analysis was done on SPSS version 20.0. Paired t-test was used to compare mean values and p valve < 0.05 was accepted as statistically significant. Results: The results of study were compared with the baseline values. The mean change in BCVA in group 1 was from 46 ± 18 letters to 52 ± 17. BCVA in group 2 was from 46 ± 18 letters to 56 ± 17 (P < 0.001). The decrease in macular edema thickness was more in group II than group I (P < 0.001). Conclusion: Macular Grid laser with or without Intravitreal Bevacizumab significantly improves vision and decreases macular edema but combined treatment led to more stable improvement in DME during follow-up. Key Words: Modified ETDRS laser, Bevacizumab, Macular edema, Anti-VEGF.